Model of Landslide Mitigation using Analytical Hierarchy Process (AHP) in Kubang Tangah Area, Sawahlunto, West Sumatra - Farid Akmal; Andriani Andriani; Bayu Martanto Adji (Universitas Islam 45, 2026)
The Kubang Tangah area in Sawahlunto, West Sumatra, has a high risk of landslides due to steep topography, high rainfall, and human activities that affect slope stability. This study aims to determine effective landslide mitigation strategies using the Analytical Hierarchy Process (AHP) method involving ten disaster experts. The three stages of mitigation analyzed include before, during, and after the disaster. The results of the investigation showed that several slope points had safety factor values below 1.25, indicating that the research location was prone to landslides. The AHP analysis produced mitigation priority weights: pre-disaster mitigation (0.41), during-disaster mitigation (0.39), and post-disaster mitigation (0.20). The main strategies prioritized in the pre-disaster stage were reforestation, construction of slope drainage systems, and determination of landslide-prone zones in spatial planning. This approach provides priority recommendations to support more targeted and efficient mitigation planning in Kubang Tangah. For the total weight, the highest mitigation value was obtained, namely, victim evacuation and repair of facilities and infrastructure (12.519), creation of evacuation routes (11.934), and determination of assembly points (10.413).